The Role of Childhood Trauma and Self-Esteem in Anxiety Disorders among Young Adults across Different Institutes of Pakistan - Mahin Taelah; Fatima Asif; Samia Noureen; Sehrish Khan (Research Journal of Psychology, 2025)
The present investigation examined how self-esteem, childhood trauma, and the emergence of anxiety disorders in Pakistani young adults relate to one another. Its specific objectives were to investigate the connections among these factors and the predictive significance of self-esteem and childhood trauma in the emerging symptoms of anxiety. 132 individuals, ages 17 to 34, from different educational institutions and mental health organizations around Pakistan participated in this quantitative research. Sample was collected through convenience sampling technique. Cross-sectional research design based correlational study was conducted for survey. Childhood trauma, self-esteem and anxiety symptoms were measured by using standardized scales; Childhood Trauma Scale–Short Form (CTQ-SF), Rosenberg Self-Esteem Questionnaire (RSES), and Generalized Anxiety Disorder Questionnaire 7-items (GAD-7). Major associations among the variables were found in the results, demonstrating that lower self-esteem was connected to higher anxiety symptoms and more levels of childhood trauma were related to lower self-esteem. While childhood trauma did not considerably indicate anxiety levels in the model, analysis of regression also revealed that low self-esteem was a major determinant of anxiety disorders. These findings emphasize the long-lasting psychological effects of negative childhood events as well as the significance of self-esteem as a mitigating psychological component in the anxiety disorders. The study highlights the necessity for early interventions aimed at enhancing self-esteem and offers insightful information for mental health practitioners dealing with populations impacted by trauma and anxiety.